Attributes of process maturity of public administration units in Poland - Krzysztof Krukowski; Magdalena Raczyńska (Administrative Sciences, 2019)
Process management is a concept that is used in public administration units in Poland to an increasing extent. Implementing this concept in public organizations, in line with the assumptions of New Public Management, is directed, among others, to increase their efficiency. The purpose of the research presented in the article was to identify the attributes describing process maturity of the community offices of urban type in Poland and to assess the interdependence of the attributes. In order to achieve the goal, an authors' questionnaire was used. Also, an attempt was made to create a process maturity model dedicated to the community offices. As a result of the conducted research, it was noticed that most of the examined entities use, at least, some elements (attributes) of process management. However, they are used at different levels by individual community offices.
Keywords: 350; process management; process maturity; process maturity models; public administration units; community office